2019
DOI: 10.1093/aje/kwz033
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Factors and Mammographic Density: Associations Among 24,840 Women and Comparison of Studies Using Digitized Film-Screen Mammography and Full-Field Digital Mammography

Abstract: Breast density is a modifiable factor that is strongly associated with breast cancer risk. We sought to understand the influence of newer technologies of full-field digital mammography (FFDM) on breast density research and to determine whether results are comparable across studies using FFDM and previous studies using traditional film-screen mammography. We studied 24,840 screening-age (40-74 years) non-Hispanic white women who were participants in the Research Program on Genes, Environment and Health of Kaise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 30 publications
0
23
1
3
Order By: Relevance
“…However, percent density was higher in parous women with BBD diagnosed prior to first birth, compared to parous women never diagnosed with BBD suggesting that there is not a protective effect of parity on density in women who have already been diagnosed with BBD prior to first birth. Women with BBD prior to first birth had a later age at first birth, which may explain why we did not observe a protective effect of parity in these women, though previous studies examining age at first birth and density have not consistently observed an association between the two (recently reviewed in [ 22 ]).…”
Section: Discussioncontrasting
confidence: 53%
“…However, percent density was higher in parous women with BBD diagnosed prior to first birth, compared to parous women never diagnosed with BBD suggesting that there is not a protective effect of parity on density in women who have already been diagnosed with BBD prior to first birth. Women with BBD prior to first birth had a later age at first birth, which may explain why we did not observe a protective effect of parity in these women, though previous studies examining age at first birth and density have not consistently observed an association between the two (recently reviewed in [ 22 ]).…”
Section: Discussioncontrasting
confidence: 53%
“…This population-based study included non-Hispanic white women in the KPNC Research Program on Genes, Environment and Health (RPGEH) who participated in a genome-wide association study of MD (33,34). The study cohort has previously been described (4,35,36). Briefly, eligible women were between the ages of 38 and 80 at mammography and had at least one screening FFDM exam during 2003 to 2013 at KPNC mammography clinics throughout Northern California, of which 36 clinics used Hologic (n ¼ 20,311) and 11 clinics used GE (n ¼ 3,881) FFDM machines.…”
Section: Study Populationmentioning
confidence: 99%
“…Mammographic breast density refers to the proportion of fibroglandular tissue (the dense area) to fatty tissue (the non-dense area) in the breast as seen on the mammogram. According to current knowledge, age and some genetic, anthropometric, reproductive or lifestyle factors are the most important determinants of MBD [3][4][5]. The results of some epidemiological studies suggest that one of the lifestyle factors likely altering breast density is cigarette smoking.…”
Section: Introductionmentioning
confidence: 99%